PERAN SWAP SYARIAH DALAM MENDUKUNG STABILITAS KEUANGAN DAN BISNIS ISLAM DI INDONESIA - Cania, Ema Saswita; Marliyah, Marliyah; Sugianto, Sugianto (International Journal Mathla’ul Anwar of Halal Issues, 2025)
This research aims to analyze the role of sharia swaps in supporting financial stability and Islamic business in Indonesia. Sharia swaps are a risk mitigation instrument designed to minimize the impact of exchange rate fluctuations in international transactions, in accordance with sharia principles. This research uses a descriptive qualitative method with a literature study approach. The data used includes primary data, such as interviews with practitioners and academics, as well as secondary data, including annual reports of Islamic banks, related regulations, and scientific journals. The analysis was carried out using thematic techniques to identify the relationship between sharia swaps and financial stability and Islamic business. The research results show that Islamic swaps provide significant benefits for Islamic financial institutions, including supporting international transactions, maintaining competitiveness, and strengthening financial stability. However, its implementation still faces challenges, such as a lack of understanding among sharia financial players, limited infrastructure, and the need for a clearer legal framework. Sharia swaps also open opportunities for further development to strengthen Indonesia's role in the global sharia financial market. The conclusion of this research is that sharia swaps not only function as a risk mitigation instrument but also as a driver of sustainable Islamic business growth. This research recommends increasing education, strengthening regulations, and collaboration between stakeholders to optimize the use of sharia swaps in Indonesia.